Experimental study on the combined application of vacuum preloading – variable-spacing electro-osmosis to soft ground improvement. Issue 1 (1st August 2016) - Fu, H.; Cai, Y.; Wang, J.; Wang, P.
Abstract : Two representative laboratory tests, using vacuum preloading alone and vacuum preloading combined with variable-spacing electro-osmosis (EO), were performed on dredged marine clay slurry used for tideland reclamation. This combined method consists of the following three stages: vacuum preloading alone, vacuum preloading in combination with large spacing EO, and vacuum preloading in combination with small spacing EO. This study focused on the feasibility and effectiveness of variable-spacing EO. The results showed that better consolidation was achieved using the combined method in terms of water content, dry density, degree of saturation, Atterberg limits, discharge of water, vane shear strength, current, and excess pore water pressure. Energy consumption for consolidation of the large spacing EO stage was less than for the small-spacing EO stage.